Coordination of Fragmentation within the International Air Law - Radzivill, Olexandr; Pyvovar, Yuriy; Sopilko, Iryna; Pyvovar, Iryna (International Journal of Engineering and Technology, 2018)
The purpose of the study is to analyze the development and branching of the directions for codification and institutionalization of international air law in the context of discussions involving fragmentation of international law. The main task of the work was to determine, on the example of international air law, the nature of the formation and codification of unified international standards in this area and their subsequent distribution of the areas of regulation and levels of specification by specialized subjects of delegated rule-making. There have been used methods of comparativistics and hermeneutics on which, first of all, the comparison and interpretation of the texts of the Paris and Chicago Conventions and their annexes have been made. It is shown that international public law has a tendency of movement from national acts through the level of bilateral agreements to the formation of agreements and regulations of the regional and global levels. This tendency is also quite clearly expressed in the history of the development of international air law. It is also determined, as a fundamental historical trend, the preservation of the dynamic inverse association between the indicated levels in the complication and branching of the directions of codification and institutionalization of international air law. This indicates the need to take into account a non-linear nature of developmental processes of any legal field, including in its characteristics complications, with the support of constant feedback between different levels of legal personality; connection of the subject area of regulation with the specific volume of competence of institutions responsible for one or another level of delegated rule-making, etc. Considering these and other aspects is important to harmonize the problems of fragmentation and to ensure the effectiveness of international law in general and international air law in particular. The connection of the fragmentation of international law is largely due to the uncertainty of the status of individual levels of delegated legal personality and inconsistency of their correlation at the level of international agreements. The problems of fragmentation, which are certainly inadmissible from the point of view of positivist legal thinking, are a source of uncertainty in many important issues that require clear coherence, regardless of conceptual approaches. From the standpoint of postpositivist concepts, it should be sought not so much in substantive codified rules, but in the effectiveness of procedural norms and the activities of the institutions responsible for reconciling the conflict of interests. However, substantive rules must be also involved in new pluralistic approaches to the law, which is not identified with the will of the state.Â Â